Psychological Nursing of Puerperae After Cesare Section: Problems and Nursing Measures - Dong, Shuyao (International Journal of Public Health and Medical Research, 2026)
Objective: To make the nursing for puerperae after cesarean section more scientific and effective, this paper analyzes the common psychological problems of puerperae after cesarean section and explores corresponding nursing interventions, so as to improve patients’ treatment compliance and quality of life. Methods: Literature review and data analysis were adopted; observations were conducted on postoperative cases; multidimensional analysis was performed on different psychological problems from the perspectives of health education, exercise, drug therapy, medical nutrition therapy, and prevention and treatment of postoperative complications, and targeted nursing measures were proposed. Conclusion: Psychological nursing plays a connecting role in the nursing process of puerperae after cesarean section. Although postoperative wound care is crucial for infection prevention, psychological nursing is vital for postpartum recovery and lactation of puerperae.